Causes and Consequences of Divorce - The Context of Kosovo - Hajdari, Egzonis; Erlüle, Fulya (Asian Journal of Social Sciences and Management Studies, 2018)
Divorce is an ancient institution of marital law that was born shortly after marriage. This institution is known by ancient laws, as well as by contemporary laws. In Kosovo the issue of divorce is regulated by Family Law. This law addresses besides principle divorce issues (divorce modalities, initiative and decision-making subjects, proceedings etc.), as well as the causes of divorces. Such issues, in an identical manner are regulated also by Turkish Civil Code. Modest results of this scientific paper indicate the fact that the issue of divorce in Kosovo constitutes a complicated and a relatively wide extent phenomenon. Consequently, in Kosovo society of these past five years (2010 – 2014) were recorded 6388 divorce cases. Divorce cases have manifested a different presence degree observing this in the context of causes determining this harmful phenomenon. Divorce whenever and wherever happens it causes numerous social and psychological consequences etc. which significantly hit spouses, their children but also society in general. During the preparation of this scientific paper we used historical-legal, legal, comparative, statistical and sampling methods.